2020
DOI: 10.1177/1076029620975502
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Thromboelastography to Identify Hypercoagulability in Lung Cancer Related Ischemic Stroke Patients

Abstract: Lung cancer related hypercoagulability could increase the risk of ischemic stroke. Routine coagulation tests may have limited capacity in evaluating hypercoagulability. The aim of this study was to investigate the ability of thromboelastography (TEG) in the identification of hypercoagulability in patients with lung cancer and cryptogenic ischemic stroke (LCIS). Between January 2016 and December 2018, whole citrated blood from LCIS patients (n = 35) and age- and gender-matched lung cancer patients and healthy v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…These findings indicate that the current definitions for hypercoagulability based on ROTEM parameters may be inadequate to describe certain clinical settings. In another study by Quan et al, the authors also evaluated the hemostatic profile of lung cancer patients, using TEG [ 27 ]. The authors reported that the Maximum Amplitude (MA), a TEG parameter similar to the ROTEM MCF, was significantly higher in cancer patients compared to age- and gender-matched controls and that the detection rate of hypercoagulability was higher for TEG compared to conventional coagulation tests.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the current definitions for hypercoagulability based on ROTEM parameters may be inadequate to describe certain clinical settings. In another study by Quan et al, the authors also evaluated the hemostatic profile of lung cancer patients, using TEG [ 27 ]. The authors reported that the Maximum Amplitude (MA), a TEG parameter similar to the ROTEM MCF, was significantly higher in cancer patients compared to age- and gender-matched controls and that the detection rate of hypercoagulability was higher for TEG compared to conventional coagulation tests.…”
Section: Discussionmentioning
confidence: 99%
“…44 TEG could identify hypercoagulability in patients with lung cancer and cryptogenic ischemic stroke significantly better than routine coagulation tests. 37 Together with platelet count greater than 50,000, normal TEG was able to predict survival in cancer patients with suspected coronary artery disease 45 and can be an independent predictive parameter for severity in lung cancer and also cancer progression as evidenced by node, and metastasis in lung adenocarcinoma than in the entire lung cancer population. 46 In gynecological cancers, there has been some contradictory findings.…”
Section: Role Of Thromboelastography In Other Cancersmentioning
confidence: 97%
“…This may denote the contribution of enhanced clot formation rather than decreased fibrinolytic activity in LCIS patients. 41 To better understand the mechanisms of cocaine use in acute stroke patients, Almaghrabi and colleagues analyzed the TEG parameters between cocaine users and non-cocaine users with either AIS or spontaneous intracerebral hemorrhage. They found that shortened median R time, reduced MA and G existed in patients of cocaine users.…”
Section: The Application Of Teg In Aismentioning
confidence: 99%
“…Meanwhile, TEG has been wildly used in bleeding events in coronary surgeries, postpartum hemorrhage, and intracerebral hemorrhage. 4 , 6 45 However, only a few studies investigated the role of TEG in bleeding events in AIS patients. Compared to CCTs, the parameter R is supposed to be superior to indicating the symptomatic intracranial hemorrhage after endovascular therapy.…”
Section: The Application Of Teg In Aismentioning
confidence: 99%